Linguistic Transformations: Animals in Plant Names - Gáll, Kinga (Universitatea Transilvania Brasov, 2025)
The naming of a plant is the basis for accurate communication among botanists. The technical, internationally accepted names are based on scientific principles that consider the taxonomic affiliation of the plant in question and focus on implicit genetic criteria. Trivial names, which are much better known than botanical names, result from an extended development and were shaped empirically, with tradition or misconception also playing a role. This article is dedicated to those plant names that contain an animal name as a component. This article examines the naming principles and motifs that apply to animal names in a botanical context, as well as the functionality of these animal names as a determining word-formation element with a transferred meaning.
Keywords: Botanical Names; Plant Names; Naming Principles; Figurative Meaning